Tren Keamanan Siber dan Evolusi Fraud Pada Sektor Perbankan di Era Digital - Jum'an; Muhammad Asyura (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2025)
The digital transformation of the banking sector has significantly optimized financial service efficiency. However, it has concurrently expanded the risks of cybercrime and fraud. Financial crimes in banking are no longer restricted to internal malfeasance, they increasingly involve external adversaries exploiting both technological vulnerabilities and human behavioral lapses. This study interrogated contemporary cybersecurity trends and the evolution of fraud modalities within the digital banking landscape. Adopting a qualitative Systematic Literature Review (SLR), this research synthesizes relevant scientific literature through the dual lenses of the CIA Triad framework and fraud theories. The findings identify a multifaceted threat landscape, ranging from ransomware and remote-work vulnerabilities to cloud-based incursions, supply chain attacks. It also targeted social engineering, such as phishing and whaling. Notably, the study highlights that social engineering remains the dominant fraud modality, exploiting the ‘human element’ as the critical vulnerability in security architectures. These results highlight that cybersecurity and fraud are inextricably linked. They require an integrated mitigation strategy that harmonizes technological safeguards, robust business processes, and human capital development to fortify digital banking resilience.